Early Life Antimicrobial Exposure: Impact on Clostridioides difficile Colonization in Infants - Chinwe Vivien Obiakor; Jaclyn Parks; Tim K. Takaro; Hein M. Tun; Nadia Morales-Lizcano; Meghan B. Azad; Piushkumar J. Mandhane; Theo J. Moraes; Elinor Simons; Stuart E. Turvey; Padmaja Subbarao; James A. Scott; et al. (MDPI AG, 2022)
The relationship between antibiotic use and Clostridioides difficile (C. difficile) has been well established in adults and older children but remains unclear and is yet to be fully examined in infant populations. This study aimed to determine the separate and cumulative impact from antibiotics and household cleaning products on C. difficile colonization in infants. This study included 1429 infants at 3-4 months of age and 1728 infants at 12 months of age from the Canadian Healthy Infant Longitudinal Development (CHILD) birth cohort. The levels of infant antimicrobial exposure were obtained from hospital birth charts and standardized questionnaires. Infant gut microbiota was characterized by Illumina 16S ribosomal ribonucleic acid (rRNA) gene sequencing. Analysis of C. difficile was performed using a quantitative polymerase chain reaction (qPCR). Overall, C. difficile colonized 31% and 46% of infants at 3-4 months and 12 months, respectively. At 3-4 months, C. difficile colonization was significantly higher in infants exposed to both antibiotics and higher (above average) usage of household cleaning products (adjusted odds ratio (aOR) 1.50, 95% CI 1.03-2.17; p = 0.032) than in infants who had the least antimicrobial exposure. This higher colonization persisted up to 12 months of age. Our study suggests that cumulative exposure to systemic antibiotics and higher usage of household cleaning products facilitates C. difficile colonization in infants. Further research is needed to understand the future health impacts.